Efficacy of hematopoietic stem cell transplantation in patients with sickle cell anemia (Research, Society and Development, 2025)
Objective: To conduct an integrative literature review on the efficacy of HSCT in the treatment of sickle cell anemia. Methodology: This is a descriptive study consisting of an analysis of theoretical reviews, gathering, evaluating, and synthesizing results within the variables expressed in the study, using PubMed/MEDLINE and SciElo databases to develop a search strategy. Results: After careful analysis, six articles were selected. These articles addressed variables such as age group, disease stage, presence of comorbidities, among others. These articles demonstrated high efficacy, especially in children under 12 years of age with an HLA-compatible donor, in addition to evaluating the good prognosis regarding successful engraftment after transplantation. Conclusion: HSCT currently represents the only curative alternative for sickle cell anemia. However, the lack of compatible donors, the high cost, and several variables hinder access to this method. Therefore, this work proves relevant not only from an academic and scientific perspective, but also offers critical and current analysis, contributing to clinical decisions and strategies that can expand access to this treatment, transforming the lives of patients.